PENGGUNAAN KHAMIR SACCHAROMYCES CEREVISEAE UNTUK MEMERBAIKI KUALITAS NUTRIEN DEDAK PADI (Using yeast saccharomyces cereviseae to improve nutrients quality of rice bran) - Maritje A. Hilakore; Mariana Nenobais; Twenfosel O. C. Dami Dato (Universitas Nusa Cendana, 2021)
The experiment was conducted to improve the nutrients quality ofrice bran fermented with Saccharomyces cereviseae.A laboratorium experimental method was used andarranging factorially in Completely Randomized Design3 x 4 x 3 namely three inoculant levels of S.cerevisiae 1, 2, and 3 % (w/w) as the first factor and inkubation time: 24, 48 and 72 hours as the second factor. Parameters observed were crude protein, soluble protein,crude fat, and phytic acid.The best result of this study was combination 2% S.cerevisiae inoculant level and 72 hours incubation time was supporting to increasing crude protein (10,88 to 14, 36%), soluble protein content (6.14 to 9.82%), and decreased phytic acid content (5.48 to 2.98%) and crude fat (8,23 to 6,91%).